A= bc(a+d)(b-c) +ac(b+d)(c-a) + ab(c+d)(a-b)
A= bc(ab+ bd -ac -dc ) + ac(bc+cd -ab-ad )+ab(ac+ad-bc-bd)
A=(ab²c + b²cd -abc² -bdc² ) + (abc² + adc² -a²bc -a²cd ) + (a²bc + a²bd - ab²c -ab²d)
A= (ab²c + cb²d -ab²c-ab²d) + (c²ab -abc² -bdc² +adc² ) + ( a²bd +a²bc -a²bc -a²cd)
A= a²(bd-cd) + b²(cd-ad) + c²(ad-bd)
A=a²d(b-c) + b²d(c-a) + c²d(a-b)
A=d(a²b-a²c + b²c-b²a +c²a-c²b)
A=d[b(a²-c²) + c(b²-a²) + a(c² - b²)]
Tacó a-c = a-c+b+b = (a-b)(b-c)
A=bc(a+d)(b-c)-ac(b+d)[(a-b)+(b-c)]+ab(c+d)(a-b)
A=bc(a+d)(b-c)-ac(b+d)(a-b)-ac(b+d)(b-c)+ab(c+d)(a-b)
A=(b-c)[bc(a+d)-ac(b+d)]+(a-b)[-ac(b+d)+ab(c+a)]
A=(b-c)(abc+bcd-abc-acd)+(a-b)(-bca-acd+abc+abd)
A=(b-c)cd(b-a)+(a-b)ad(b-c)
A=(b-c)(b-a)(cd-ad)
A=(b-c)(b-a)d(c-a)=d(b-c)(b-a)(c-a)